Social network and social normative characteristics of married female adolescents in Dosso, Niger: Associations with modern contraceptive use - Shakya, Holly B. (Glob Public Health, 2020)
In this study we analyzed the social networks of a systematic sample of married adolescent girls (ages 13–19 years) residing in Dosso, Niger (N=322); data were collected as part of an evaluation of a family planning (FP) intervention. Participants were asked to name individuals important in their lives (alters) using three name generating questions as part of a larger survey including questions about reproductive health, social norms, and FP. Each girl was asked specific questions about their alters. One alter per girl was then recruited to be separately interviewed (N=250), using a subset of questions asked of the primary respondent. This provided us with two separate datasets: one in which we have data from each respondent regarding each person that they nominated, and one in which we have the interviewed alters matched with the respondent who nominated them. We found that married adolescent girls who were nulliparous were more likely to have no alters, and that those with the most alters had participated in the intervention. Alters of treatment participants were more likely to have used FP. Respondents were more likely to have used FP when their sisters or in-laws had, but there was no correlation with use by friends. Our results provide evidence of diffusion of the FP program to those close to intervention participants. Future research should explicitly study these dynamics, as they are crucial to understanding intervention costing, impact, and the possibility of normative change.